2013
DOI: 10.1186/1478-811x-11-35
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a novel specific neuroglial integrin signaling pathway increases STAT3-mediated CNTF expression

Abstract: BackgroundCiliary neurotrophic factor (CNTF) expression is repressed in astrocytes by neuronal contact in the CNS and is rapidly induced by injury. Here, we defined an inhibitory integrin signaling pathway.ResultsThe integrin substrates laminin, fibronectin and vitronectin, but not collagen, thrombospondin or fibrinogen, reduced CNTF expression in C6 astroglioma cells. Antibodies against αv and β5, but not α6 or β1, integrin induced CNTF. Together, the ligand and antibody specificity suggests that CNTF is repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 121 publications
5
57
0
Order By: Relevance
“…It remains to be determined which pathways downstream of FAK might be involved, but could include the serine kinases JNK1 [22] or ERK [73]. The latter is also activated by HGF [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be determined which pathways downstream of FAK might be involved, but could include the serine kinases JNK1 [22] or ERK [73]. The latter is also activated by HGF [34].…”
Section: Discussionmentioning
confidence: 99%
“…We recently discovered an integrin signaling pathway that inhibits CNTF expression, involving FAK, JNK and the S727 residue of the transcription factor STAT3 [22]. Depending on phosphorylation of residues S727 or Y705, STAT3 can inhibit or promote nuclear gene expression [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that integrin-FAK signaling promotes STAT3 phosphorylation specifically on the S727 residue [21]. Here, ER stress induced by TG and TM caused a reduction in phosphorylation of the key Y397 residue of FAK, as early as 24 h (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…We recently identified an FAK-STAT3 pathway that activates the S727 residue of STAT3 [21], and determined that FAK inhibition caused dramatic changes in mitochondrial bioenergetic function [26]. Here, the ER stress-induced loss of pS727-STAT3 coincided with reductions in pFAK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation